A PIONEER EXAMPLE OF STEEL FRAME CONSTRUCTION IN OTTOMAN ARCHITECTURE: THE GREAT SYNAGOGUE OF EDIRNE - Erdem, Ayten; Yergun, Uzay; Seckin, Nadide (DOLNOSLASKIE WYDAWNICTWO EDUKACYJNE-DWE, 2012)
The Great Synagogue located in the inner citadel area of Edirne in Turkey is an Ottoman-period Jewish house of worship. Built in 1906 by the French architect France Dapree, the synagogue was abandoned in 1983 when the Jewish population of the city diminished. The synagogue's plan resembles that of a tri-partite basilica. The entry to the building is through a portico reached via stone steps. Single-storied in part and double-storied in other areas, the building's entry and main hall are wrapped with a gallery. The staircases to this gallery are situated within tall tower-like structures located on the front corners of the structure. The structure is topped with a gable roof covered with Marseille tiles. The lighting in the middle section of the main hall is accentuated with a cloistered vault situated in the middle of the building. The synagogue construction is based on a mixed technique made up of load-bearing walls and a steel framework. While the body walls are brick, the gallery floor, roof and vault are supported by I-beams faced with brick. Also, the I-beams supporting the roof are connected to the side body walls and the beams faced with brick. The Grand Synagogue is especially significant as it represents one of the first examples Of the use of the steel frame system in the early 20th century in the Ottoman Empire. This work will investigate the construction details of the Grand Synagogue, a building that differs from the earlier Ottoman building traditions, and will both document and determine any problems related to its preservation.
Keywords: Ottoman architecture; Synagogue; Steel frame construction; Construction & Building Technology; Engineering